Vancomycin population pharmacokinetics and dosing proposal for the initial treatment in obese adult patients - Polášková, Lucie; Murínová, Irena; Gregorová, Jana; Slanař, Ondřej; Šíma, Martin (Frontiers in Pharmacology, 2024)
The aim of this study was to develop vancomycin population pharmacokinetic model in adult obese patients, and to propose covariate-based dosing individualization in order to maximize the achievement of newly recommended PK/PD target according to a revised consensus guideline from 2020.Methods: Therapeutic drug monitoring data from initial vancomycin therapy (first 3 days of treatment) in adult obese (BMI ≥ 30 kg/m 2 ) patients from 2013 to 2022 were analysed using a non-linear mixed-effects modelling method and Monte Carlo simulations were then used to find optimal dosage maximizing the PK/PD target attainment. Results: A total of 147 vancomycin serum levels obtained from 138 patients were included to the analysis. Based on covariate model diagnosis among all tested variables, no reliable predictor of vancomycin volume of distribution (Vd) was identified, while clearance (CL) was positively correlated with eGFR and lean body mass. Creatinine based-eGFR predicted vancomycin CL better than cystatin C-based eGFR. The median (interquartile range) value from conditional modes of individual estimates of Vd, CL and elimination half-life in our population was 74.0 (70.5-75.4) L, 6.65 (4.95-8.42) L/h and 7.7 (6.0-10.0) h, respectively. Conclusion: We proposed dosing individualization based on covariate found in order to maximize the achievement of newly recommended PK/PD target of AUC/MIC ratio of 400-600. Clinical pharmacy/pharmacology intervention may lead to improvement of vancomycin dosing with reflection in PK/PD target attainment.